Deposition of Fibrinogen on the Surface of in vitro Thrombi Prevents Platelet Adhesion - Owaynat, Hadil (Thromb Res, 2015)
The initial accumulation of platelets after vessel injury is followed by thrombin-mediated generation of fibrin which is deposited around the plug. While numerous in vitro studies have shown that fibrin is highly adhesive for platelets, the surface of experimental thrombi in vivo contains very few platelets suggesting the existence of natural anti-adhesive mechanisms protecting stabilized thrombi from platelet accumulation and continuous thrombus propagation. We previously showed that adsorption of fibrinogen on pure fibrin clots results in the formation of a nonadhesive matrix, highlighting a possible role of this process in surface-mediated control of thrombus growth. However, the deposition of fibrinogen on the surface of blood clots has not been examined. In this study, we investigated the presence of intact fibrinogen on the surface of fibrin-rich thrombi generated from flowing blood and determined whether deposited fibrinogen is nonadhesive for platelets. Stabilized fibrin-rich thrombi were generated using a flow chamber and the time that platelets spend on the surface of thrombi was determined by video recording. The presence of fibrinogen and fibrin on the surface of thrombi was analyzed by confocal microscopy using specific antibodies. Examination of the spatial distribution of two proteins revealed the presence of intact fibrinogen on the surface of stabilized thrombi. By manipulating the surface of thrombi to display either fibrin or intact fibrinogen, we found that platelets adhere to fibrin- but not to fibrinogen-coated thrombi. These results indicate that the fibrinogen matrix assembled on the outer layer of stabilized in vitro thrombi protects them from platelet adhesion.